AKTIVITAS PERDAGANGAN DI KERESIDENAN JEPARA 1843-1891 (Paramita: Historical Studies Journal, 2015)
When the role of Jepara as a trading city deteriorated from the beginning 19th century, the life of Jepara Residency community shifted from maritime sector with a trading base to agrarian sector. The shift to agrarian sector which based on agriculture and plantation, and supported by the sea outputs made this residency attractive for traders. Both local traders, neighboring traders around Jepara, foreign eastern traders and interinsuler, as well as European traders. The traded products were exported to the surrounding areas of the residency, outer islands of Java, Singapore, and Europe. The export activities were carried out to other places through Semarang and Surabaya ports. In addition, the import activities also took place because this residency was a potential section in marketing imported products. It shows that in 19th century, especially around 1843 to 1891 the trading activities in Jepara Residency was still in existence.Keywords : Activity, Trading, Residency, Jepara Residency, Export, ImportMeredupnya Jepara sebagai kota dagang sejak awal abad ke-19 membuat kehidupan masyarakat Keresidenan Jepara beralih dari sektor maritim yang berbasis perdagangan ke sektor agraris. Beralihnya ke sektor agraris yang berbasis pada pertanian,  perkebunan, dan  ditopang oleh hasil laut justru membuat Keresidenan ini mempunyai daya tarik bagi pedagang. Baik pedagang lokal, pedagang sekitar wilayah Jepara, pedagang Timur Asing dan interinsuler, maupun pedagang Eropa. Produk yang diperdagangkan di-ekspor ke wilayah sekitar Keresidenan, interinsuler,  Singapura, dan Eropa. Kegiatan ekspor ke interinsuler dan ke luar negeri dilakukan melalui pelabuhan Semarang dan Surabaya. Selain itu, kegiatan impor juga berlangsung karena keresidenan ini merupakan  pangsa potensial dalam memasarkan produk impor. Ini menunjukkan bahwa pada abad ke-19, terutama sekitar tahun 1843 hingga 1891 aktivitas  perdagangan di keresidenan Jepara masih tetap eksis.Keywords : Aktivitas, perdagangan, Keresidenan Jepara, ekspor, impor